(untitled) (Global Journal of Management and Business Research, 2022)
The purpose of this study was to establish principals#x2019; attitudes towards guidance and counselling services and maintenance of discipline in secondary schools. It further sought to establish whether principals#x2019; gender, age, training, teaching and administrative experiences have any effect on their attitudes. Questionnaires, Interview and observation schedules were used to collect data. The researcher used Spearman Brown Prophecy to determine the research instruments#x2019; reliability which 0.95. Split- half method was used to determine the Coefficient of Internal Consistency whose values varied between 0.00 and +1.00. The closer the value was to +1.00, the stronger the congruency measure whose value was 0.9 and above hence were reliable. Two-tailed T-test and One Way analyses of Variance (ANOVA) were used to analyze data whose results showed that 24.4% of the principals were conversant with the objectives of guidance and counselling services. However, they were not conversant with the role of teacher- counsellors working in their schools who they said did not have any formal training. The study recommended that Principals and teachers be trained through regular in-service courses, seminars and workshops. Besides, further research need to be done on causes of unrest and abuse of drugs in schools.